Targeting E2 ubiquitin-conjugating enzyme UbcH5c by small molecule inhibitor suppresses pancreatic cancer growth and metastasis - Simin Qi; Xiaoqing Guan; Jia Zhang; Dehua Yu; Xuefei Yu; Qinglin Li; Wenjuan Yin; Xiang-Dong Cheng; Weidong Zhang; Jiang-Jiang Qin (Molecular Cancer, 2022)
Abstract Background Pancreatic cancer is one of the most lethal cancers worldwide. The IAPs function as E3 ubiquitin ligases and contribute to pancreatic cancer initiation, progression, and metastasis. Although IAP-targeted therapies have been developed and shown anticancer efficacy in preclinical settings, none of them has been approved yet. Methods Transcriptome data from public datasets were used to analyze the correlation of IAPs and E2s, and the biological function of E2 UbcH5c in pancreatic cancer. A structure-based virtual screen was used to identify UbcH5c inhibitor, and surface plasmon resonance analysis and cellular thermal shift assays were employed to evaluate the binding affinity. The anticancer activities were demonstrated through in vitro and in vivo assays, while the related mechanisms were explored through transcriptomic and proteomic analyses and confirmed by western blot, immunofluorescence, and qRT-PCR. Results UbcH5c is positively correlated with the expression of IAPs in pancreatic cancer. We further found that UbcH5c is overexpressed and associated with a poor prognosis in pancreatic cancer. We identified a small-molecule UbcH5c inhibitor, termed DHPO, which directly bound to UbcH5c protein. DHPO inhibited cell viability and colony formation, induced apoptosis, and suppressed migration and invasion of pancreatic cancer cells in vitro. The compound inhibited UbcH5c-mediated IκBα degradation and NF-κB activation, which is critical for its anticancer activity. Furthermore, DHPO suppressed the tumor growth and metastasis in two orthotopic pancreatic tumor mouse models. Conclusions These results indicated that inhibiting UbcH5c is a novel and effective strategy for treating pancreatic cancer and DHPO represents a new class of UbcH5c inhibitor and may be further developed as an anti-pancreatic cancer therapeutic agent.